ChemInform Abstract: New Pathways Towards Efficient Metallic Spin Hall Spintronics. Issue 3 (29th December 2015) - Jungfleisch, Matthias Benjamin; Zhang, Wei; Jiang, Wanjun; Hoffmann, Axel
Abstract: Review: 112 refs.